Centro Agroindustrial Y De Capacitación En producción Panelera. Corregimiento De San Bernardo Ibagué - Tolima (2023)
The agro-industrial center for panelera training and production is a facility specialized in the formation and production of products derived from cane sugar, especially panela. This project is dedicated to providing training and training for farmers and workers in the panelero sector, as well as to carry out Panela production processes efficiently and with high quality.